The current refugial rainforests of Sundaland are unrepresentative of their biogeographic past and highly vulnerable to disturbance - Cannon, Charles H. (National Academy of Sciences, 2009)
Understanding the historical dynamics of forest communities is a critical element for accurate prediction of their response to future change. Here, we examine evergreen rainforest distribution in the Sunda Shelf region at the last glacial maximum (LGM), using a spatially explicit model incorporating geographic, paleoclimatic, and geologic evidence. Results indicate that at the LGM, Sundaland rainforests covered a substantially larger area than currently present. Extrapolation of the model over the past million years demonstrates that the current “island archipelago” setting in Sundaland is extremely unusual given the majority of its history and the dramatic biogeographic transitions caused by global deglaciation were rapid and brief. Compared with dominant glacial conditions, lowland forests were probably reduced from approximately 1.3 to 0.8 × 10(6) km(2) while upland forests were probably reduced by half, from approximately 2.0 to 1.0 × 10(5) km(2). Coastal mangrove and swamp forests experienced the most dramatic change during deglaciations, going through a complete and major biogeographic relocation. The Sundaland forest dynamics of fragmentation and contraction and subsequent expansion, driven by glacial cycles, occur in the opposite phase as those in the northern hemisphere and equatorial Africa, indicating that Sundaland evergreen rainforest communities are currently in a refugial stage. Widespread human-mediated reduction and conversion of these forests in their refugial stage, when most species are passing through significant population bottlenecks, strongly emphasizes the urgency of conservation and management efforts. Further research into the natural process of fragmentation and contraction during deglaciation is necessary to understand the long-term effect of human activity on forest species.